PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA MELALUI PENDEKATAN INQUIRI PADA SISWA KELAS IV SD NEGERI WONOYOSO - Sukma, Ely Sarantika (Universitas Negeri Semarang, 2017)
The purpose of this ‘CLASS MOVE’ research is for rising student’s motivation and report grade on science subjects class IV SD Negri Wonoyoso through inquiry approach. This class move research held on first even semester 2016/2017 in SD Negri Wonoyoso UPTD district Pringapus, Semarang city, on class IV. Research held during three days, start from date 21, 22, until 23. Amount 31 students join this research, consist of 13 female students and 18 male students. object of this study are: 1. Motivation 2. lerned low student learning outcomes are low and under the KKM 3. Inquiry spproach. The method used in this classroom action research consisted of two cycles, each cycle consists of four stages, namely, planning, implementation, observation, and reflection observations. In this action researchers used data collection tool in the form of tests, observation sheets, documentation lists the value and personal records of students to know the initial conditions of student’s motivation in learning activities.The results showed that through the inquiry approach can increase learning motivation in science subjects about style for grade IV SDN Wonoyoso in the 2nd semester year 2016/2017, from the initial conditions in science subjects students had very low motivation, until the final conditions students’s motivation is very high. In addition, through the inquiry approach can also improve learning outcomes for students IPA. from the initial conditions of grade report average of 60 to the final condition average 72,16, and it increased by 20.27%. It can be concluded that through the inquiry approach can improve grade report on science subjectand built motivation for class IV semster 2 year 2016/2017 in SDN Wonoyoso.